Kampanye Public Relations (Edukasi dan Kolaborasi) dalam Tingkat Kesadaran Masyarakat Akan Penggunaan Air Bersih : (Studi Deskriptif Kualitatif Pada Sobat Air Jakarta) - Azzahra Alamsyah; Lilik Sumarni (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Sobat Air Jakarta is a community communication forum for sharing various information about waters in Jakarta. Based on the spirit of education and collaboration, where the educational pillar in question is Sobat Air Jakarta distributing all forms of education related to Jakarta's water resources to the community. Information is currently provided through social media Instagram and through offline events. Sobat Air Jakarta, through its program, invites the public to be more aware of the use of clean water. The qualitative research method is a research method based on the philosophy of postpositivism, applied to research the condition of natural objects, where the key instrument of this research is the researcher, data collection techniques are carried out in combination. , inductive data analysis, with qualitative research results that focus more on meaning than generalization. The campaign carried out by Sobat Air Jakarta through the education provided, it is hoped that awareness of the importance of protecting water sources can become part of the collective consciousness of the people of Jakarta. Apart from providing understanding, campaigns can also be a tool to change people's attitudes and behavior regarding water management. The "Education and Collaboration" public relations campaign carried out by Sobat Air Jakarta has succeeded in creating deeper awareness and concern among the public regarding the importance of clean water management. Through an effective communication strategy, including a deep understanding of the demographics of the target audience and the choice of appropriate communication channels via Instagram social media, the campaign messages were successfully conveyed to the intended audience.